(untitled) (Nigerian Journal of Technology, 2018)
The possibility of using Albizia saman pod activated carbon (ASPAC) as an adsorbent in fixed down flow adsorption columns to remove Cd (II) from wastewater was investigated for the purpose of converting the waste to a valuable product. The effects of impregnation ratio, particle size, carbon height, pressure head and initial cadmium Cd (II) concentration on the adsorption of Cd (II) from wastewater were investigated. The obtained adsorption data from the experiment was then fitted into the Hutchin’s bed depth service time (BDST) model to study the columns performance at 15% and 90% breakthrough concentrations. The BDST model constants were determined. An optimal pressure head of 5 cm, impregnation ratio of 1:6, packing height of 3.5 cm, particle size of 75 µm and initial Cd (II) concentration of 0.029 mg/L were found to be the most effective combination, which removed 100 % of the Cd (II) within a service time of 14 hrs. There was a gradual decrease in the percentage of adsorbed Cd (II) with time; the percentage adsorbed became zero at 44, 56 and 86 hours respectively for 2.5 cm, 3 cm and 3.5 cm carbon heights. The breakthrough curves for Cd (II) adsorption maintained the characteristic S-curve for most dynamic studies. Chi-squared test performed on the developed BDST models revealed the goodness of fit of the models for the prediction of the columns performance at all breakthrough concentrations investigated. The use of ASPAC as adsorbent for the removal of Cd (II) from wastewater in adsorption columns is therefore recommended. http://dx.doi.org/10.4314/njt.v37i3.37